2004
DOI: 10.1124/mol.65.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Invasive Gene Expression Profile of Curcumin in Lung Adenocarcinoma Based on a High Throughput Microarray Analysis

Abstract: Curcumin has been reported to exhibit anti-invasive and/or antimetastatic activities, but the mechanism remains unclear. In this study, microarray analysis of gene expression profiles were used to characterize the anti-invasive mechanisms of curcumin in highly invasive lung adenocarcinoma cells (CL1-5). Results showed that curcumin significantly reduces the invasive capacity of CL1-5 cells in a concentration range far below its levels of cytotoxicity (20 M) and that this anti-invasive effect was concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 32 publications
2
62
1
1
Order By: Relevance
“…Moreover, the impact of 1 mM curcumin on gene expression was equally restricted. Unlike previously reported gene array data using higher concentrations of curcumin (60), no evidence of induction of Nrf2-responsive genes such as the antioxidant genes, or suppression of pro-inflammatory gene sets, was evident. This would help explain the limited impact that low concentrations of curcumin (, 1 mM) alone would have on ROSinduced inflammation, whether or not LPS was also present.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the impact of 1 mM curcumin on gene expression was equally restricted. Unlike previously reported gene array data using higher concentrations of curcumin (60), no evidence of induction of Nrf2-responsive genes such as the antioxidant genes, or suppression of pro-inflammatory gene sets, was evident. This would help explain the limited impact that low concentrations of curcumin (, 1 mM) alone would have on ROSinduced inflammation, whether or not LPS was also present.…”
Section: Discussioncontrasting
confidence: 99%
“…The human lung carcinoma cell line, A549 [American Type Culture Collection (ATCC); CCL-185], was obtained from ATCC. The cells were grown in DMEM (Life Technologies) supplemented with 10% fetal bovine serum (FBS; Life Technologies) and each of penicillin and streptomycin (100 mg/mL each) at 37jC in a humidified atmosphere of 5% CO 2 (7).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…This might be possible by synergistically modulating several of the properties of cancer such as proliferation, invasion, and metastasis. To provide a more global perspective, we examined the anticancer mechanisms of curcumin using cDNA microarray mRNA analysis of lung cancer cells and identified a panel of candidate curcumin target genes (7). Some of these target genes are highly associated with the cancer invasion and metastasis (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the cell viability of 95-D cells at 0, 5, 10, and 20 μg/ ml of GA-Me was 98.3 ± 2.9%, 96.4 ± 0.6%, 93.1 ± 2.3%, and 92.4 ± 1.8%, respectively (data not shown). Apoptosis of tumor cells was only 2.3% at 20 μg / ml of GA-Me for 24 h. These results can be compared to the reported data on curcumin: Exposure of CL1-5 cells, which have high invasive capacities, to curcumin (0, 1, 5, 10, 20 μM) influenced the cell viability of CL1-5 cells in a concentration-dependent manner (92.3 ± 6.1% at 10 μM and 70.1 ± 7.3% at 20 μM), and curcumin (1 -20 μM) could significantly inhibit cell invasion of CL1-5 cells (56.0 ± 16.1% at 1.0 μM) (13).…”
mentioning
confidence: 96%